Cutaneous Structural and Biochemical Correlates of Foot Complications in High-Risk Diabetes - Tahrani, Abd A. (American Diabetes Association, 2012)
OBJECTIVE: Impairment of skin quality may contribute to diabetic foot ulceration (DFU). Our goal was to determine whether high-risk patients exhibited specific skin structural and metabolic deficits that could predispose to foot complications. RESEARCH DESIGN AND METHODS: A total of 46 patients comprising 9 diabetic control subjects, 16 with diabetic peripheral neuropathy (DPN) alone, and 21 with recurrent DFUs (including 9 with Charcot neuroarthropathy [CNA]) were recruited and compared with 14 nondiabetic control (NDC) subjects. DPN was assessed using the Michigan Neuropathy Screening Instrument (MNSI). Skin punch biopsies (3 mm) were performed on upper and lower leg skin for measurements of intraepidermal nerve fiber density (IENFD), structural analysis, type 1 procollagen abundance, tissue degrading matrix metalloproteinases (MMPs), and poly(ADP-ribose) (PAR) immunoreactivity. RESULTS: MNSI scores were comparable across DPN groups. IENFD was decreased by diabetes and DPN but did not differ between neuropathic groups. Skin structural deficit scores were elevated in all neuropathic subjects, particularly in the DFU group. Type 1 procollagen abundance was reduced in DFU subjects 387 ± 256 units (mean ± 1 SD) compared with NDC subjects (715 ± 100, P < 0.001). MMP-1 and MMP-2 were activated by diabetes. PAR immunoreactivity was increased in DFU (particularly in the CNA group; P < 0.01) compared with other DPN subjects. CONCLUSIONS: Increased PAR, reduced type 1 procollagen abundance, and impaired skin structure are associated with foot complications in diabetes. The potential of therapies that improve skin quality to reduce DFU needs to be investigated.